Expert System for Diagnosing Areca Plant Diseases Using the Certainty Factor Method - Indrayani, Lilis; Zulkarnain, Zulkarnain; Kamesrar, Magrid Margaretha (ISB Atma Luhur, 2023)
Areca nut is a plant that is cultivated by the people of Papua as a means of livelihood. Areca nut has many benefits, starting from the fruit, leaves, roots, and the economic value of betel nut is also quite good. The problem often encountered by areca cultivators is the damage caused by areca plant diseases, causing losses both in terms of yield and control. In this study, the expert system for diagnosing areca plant diseases uses the Certainty Factor method, the essence of this method is to measure whether it is certain or uncertain in diagnosing disease based on the type of disease and disease symptoms found in areca plants, there are 8 types of areca plant diseases, namely spotting and yellowing, red leaf rust, stem base rot, fruit rot, shoot rot, root rot, flower and leaf fall and stunted plants. With the problems that occur, researchers will create an expert system that can help areca nut cultivators in diagnosing diseases in areca palm plants, it is hoped that this system can help areca cultivators by applying the Certainty Factor method which adopts expert knowledge into a computerized system so that the system can solve problems like an expert.